2008
DOI: 10.1111/j.1460-9592.2008.02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal mask airway insertion in children: comparison between rotational, lateral and standard technique

Abstract: A rotational technique with partially inflated cuff is associated with the highest success rate of insertion and lowest incidence of complications and could be the technique of first choice for LMA insertion in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 22 publications
1
59
1
Order By: Relevance
“…This may be because of our technique as we inserted the LMA with inflated cuff while its lumen facing laterally forces the mouth to open wider and keeps the tongue from being pushed back into the air passage which results in easy insertion. Ghai et al in a review showed that there is a high success rate at first attempt whereas time required for successful insertion and incidence of trauma are less in rotational technique compared to lateral and standard technique in children which is not similar to our study [20]. It may be because of the anatomical difference of airway between adult and children: a relatively large tongue, a relatively large and flappy epiglottis, a cephalad and more anterior larynx and more acute angle of posterior pharyngeal wall to the floor of mouth [23].…”
Section: Many Anesthesiologists Do Not Use the Brain Technique Properlycontrasting
confidence: 90%
“…This may be because of our technique as we inserted the LMA with inflated cuff while its lumen facing laterally forces the mouth to open wider and keeps the tongue from being pushed back into the air passage which results in easy insertion. Ghai et al in a review showed that there is a high success rate at first attempt whereas time required for successful insertion and incidence of trauma are less in rotational technique compared to lateral and standard technique in children which is not similar to our study [20]. It may be because of the anatomical difference of airway between adult and children: a relatively large tongue, a relatively large and flappy epiglottis, a cephalad and more anterior larynx and more acute angle of posterior pharyngeal wall to the floor of mouth [23].…”
Section: Many Anesthesiologists Do Not Use the Brain Technique Properlycontrasting
confidence: 90%
“…The current investigation has addressed this by using the lateral insertion technique [10], which has a higher reported success rate in children [9,10] than the Brain's technique. Despite making this change, the rate of successful LMA insertion remains similar to that we previously reported, and comparable to success rates reported for adult cardiac arrest [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Two main limitations of that study are first, the practitioners were relatively experienced with facemask ventilation and as such may not be representative of first responders to cardiopulmonary arrests in children. Second, the method of LMA insertion that was taught was the method advocated by Brain in adults and this may not be optimal, studies having shown that the lateral insertion technique has a higher success rate in children [9][10][11].In view of these limitations we have repeated our randomised crossover trial, comparing the LMA with the facemask and oropharyngeal airway for manual ventilation of the lungs of apnoeic anaesthetised children. We studied ward based paediatric nurses as our cohort of practitioners as we felt their skills were more likely to be representative of first responders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported success rates of 67-93% for the first attempt at inserting LMA. [4][5][6] In addition, a degree of skill is required to place LMA correctly, and suboptimal positioning of the device can give rise to such problems as air leakage or airway obstruction. Various techniques have been described to ensure a high successful insertion rate.…”
Section: Introductionmentioning
confidence: 99%